Religious identities in antiquity and the Early Middle Ages: walking together & parting ways - Lindstedt, Ilkka; Nikki, Nina; Tuori, Riikka (Studies on the children of Abraham, 2022)
"Religious Identities in Antiquity and the Early Middle Ages contains eight thought-provoking articles that discuss the formation of antique and early medieval religious identities and ideas in rabbinic Judaism, early Christianity, Islam, and Greco-Roman culture. The articles question the artificial disciplinary and conceptual boundaries between traditions. Instead, they stress their shared nature. The collection is a result of discussions at the international symposium "Ideas and Identities in Late Antiquity: Jews, Christians, and Muslims" at the Helsinki Collegium for Advanced Studies on March 12-13, 2018"--